Philosophers and the Problem of the Existence of the World (Al-Farooq Journal of Sciences, 2026)
This research addresses an important philosophical issue that has occupied philosophers throughout the ages and has received extensive scholarly attention, namely the existence of the world.The study aims to identify the most significant philosophical viewpoints concerning this issue, with particular emphasis on the perspective of Aristotle, whose ideas exerted a profound influence on subsequent philosophers. The research examines this problem within ancient philosophy and medieval philosophy, while also highlighting Plotinus’s view regarding the manner in which the world emanated from God through the theory of emanation and procession, a theory that later had a considerable impact on Muslim philosophers. They found in it a means of reconciling Aristotle’s doctrine of the eternity of the world with the religious belief in its creation.The study further reviews the views of Al-Farabi and Ibn Sina (Avicenna) as representative models of Islamic philosophy. It also discusses the position of Abu Hamid Al-Ghazali on this issue, whose views differed significantly from those of the philosophers. Al-Ghazali launched a vigorous critique against them, arguing that their doctrines conflicted with the principles of religion and Islamic law.Finally, the conclusion presents the most important findings and results derived from this study.